Sublethal Effects of Metaflumizone on Plutella xylostella (Lepidoptera: Plutellidae) - Zhe ZHANG; Jian-hong LI; Xi-wu GAO (Journal of Integrative Agriculture)
Metaflumizone is a novel sodium channel blocker insecticide, which has been registered for controling the diamondback moth (DBM), Plutella xylostella (Lepidoptera: Plutellidae) in China. It is unavoidable for DBMs to be exposed to sublethal dose of metaflumizone in brassicaceous vegetable field. Sublethal effects of metaflumizone at LC15 (1.06 mg L−1) and LC25 (2.03 mg L−1) on the biological characteristics were investigated. Pupation rate, pupal period and pupal weight were significantly declined comparing with the control (P=0.05) when third instar larvae were exposed to LC15 and LC25 of metaflumizone. Comparing the control group to LC15 and LC25 treatment groups, there were significant differences in the development periods of eggs, first instar larvae, pupae and total preoviposition period. The peak of age-specific fecundity in LC15 and LC25 treatment groups was lagged behind control group. Mean values of intrinsic rate of increase (rm), net reproductive rate (R0) and finite rate of increase (λ) observed from the LC15 and LC25 treatment groups were lower than those from the control group. But mean values of gross reproduction rate (GRR) was not different. The mean generation time (T) of the treatment groups was prolonged. Whether sublethal doses of metaflumizone could stimulate reproduction in the long term needs further investigation on continuous generations.